2021
DOI: 10.1016/j.cjco.2021.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ablation in Prevention of Recurrent Implantable Cardioverter Defibrillator Shocks in Patients With Tetralogy of Fallot

Abstract: Background: Implantable cardioverter defibrillators (ICDs) are effective in preventing arrhythmic sudden cardiac death in patients with tetralogy of Fallot (TOF). Although ICD therapies for malignant ventricular arrhythmias can be life-saving, shocks could have deleterious consequences. Substrate-based ablation therapy has become the CJC Open 3 (2021) 619e626

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In TOF patients with ICDs implanted for SCD prevention, >80% of appropriate shocks are delivered for monomorphic VT [70,71]. ICDs can effectively terminate ventricular arrhythmias but do not prevent them and, as mentioned above, have an increased risk of complications.…”
Section: Ablation Of Vtmentioning
confidence: 99%
See 2 more Smart Citations
“…In TOF patients with ICDs implanted for SCD prevention, >80% of appropriate shocks are delivered for monomorphic VT [70,71]. ICDs can effectively terminate ventricular arrhythmias but do not prevent them and, as mentioned above, have an increased risk of complications.…”
Section: Ablation Of Vtmentioning
confidence: 99%
“…A minority of patients exhibit an alternative source of VT, such as conduction bundles or focal sites within the left or right outflow tracts that are also amenable to ablation [52]. Several studies have demonstrated that radiofrequency catheter ablation reduces the risk of VA, ICD shocks, and SCD in patients with sustained VT [70,71]. Moreover, the 12 lead VT ECG was shown to be a noninvasive predictor of the involved AI: most RBBB VTs were due to clockwise activation of AI3 while most LBBB VTs were due to clockwise activation of AI3 if precordial transition was <V5 while a transition of ≥V5 was due to AI1 or AI3 involvement [72].…”
Section: Ablation Of Vtmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Role of Ablation for Secondary Treatment of Clinical VT Among patients with repaired TOF implanted with an ICD for secondary prevention, the proportion of those who received the device for a nonfatal monomorphic VT exceeds 70%. 14,38 In patients with ICDs, >80% of appropriate therapies are delivered for monomorphic VT. 14,74 ICDs effectively terminate but do not prevent VA and come with complications such as high rates of inappropriate ICD shocks, lead dysfunction, and infection. 2,38 Despite the availability of antitachycardia pacing, ≈40% of patients require ICD shocks to terminate the predominantly fast VTs (median VT cycle length, 290 milliseconds).…”
Section: Icd Complicationsmentioning
confidence: 99%
“…Radiofrequency catheter ablation is an important adjunctive treatment option to control recurrent monomorphic VT and to prevent ICD shocks. 37,[74][75][76][77] The dominant VT substrate, namely SCAI, can be identified during stable rhythm without the need for VT induction. Accordingly, despite hemodynamic intolerance, isthmus-dependent VTs can be ablated with low rates of VT recurrence if conduction block in the isthmus is achieved.…”
Section: Icd Complicationsmentioning
confidence: 99%